Modulations of calcium binding and of energy coupling by the calcium pump of sarcoplasmic reticulum - Meltzer, Sybella (Department of Chemistry, 2020)
The sarcoplasmic reticulum (SR) of striated muscle plays a central role in control of contractile activity. It acts as an intracellular sink for calcium during relaxation and releases cav2 + during contraction. This highly differentiated endoplasmic reticulum is a self-contained network with a continuous hollow interior which surrounds each muscle fibril (Fig. 1) (Porter, 1961). The SR is fragmented at longitudinal intervals of one sarcomere in length by the transverse tubular or T-tubular system (Porter, 1961; Franzini-Armstrong, 1980). On each side of the T-tubules there are enlarged areas known as cisternae, with branched areas between the cisternae known as the longitudinal elements. The juncture of the three membranes (two terminal cisternae and one Ttubule) is referred to as the triad. The junction between the SR and • 0 the T-tubules is known as a junctional gap and has.a width of 100-200 A. Periodic densities, referred to as 'feet', cross the junctional gap to join the SR and T-tubular membranes (Franzini-Armstrong, 1980). Direct communication between the SR, the T-tubules and the feet have been postulated (Schneider· and Chandler, 1973; Mathias et al., 1979). The view has developed, starting with the experiments of Huxley and Taylor (1958) and Huxley and Straub (1958), that, under physiological conditions, contraction in skeletal muscle is triggered by depolarisation of the membranes of the T-tubules. This results in the release of ca 2 + into the myoplasm from its intracellular storage location, the SR, and thus activating the contractile proteins (Schneider and Chandler, 1973). (See Fuchs (1974) and Ebashi (1980) for a review on the possible mechanism involved in excitation-contraction coupling.)